(untitled) (Research, Society and Development, 2021)
Spinal cord injury is a devastating condition that leads to significant disabilities. The treatment for this problem is a challenge in neuroscience, and it is necessary to combine different strategies to obtain functional recovery outcomes. There are many herbal natural products, such as Croton blanchetianus Baill (CB) essential oil, a Brazilian semi-arid bush with neuroprotective substances tested in regeneration processes and synaptic plasticity. Thus, this study analyzed the cellular plasticity of spinal cord neurons and glial cells in the presence of sciatic nerve-conditioned medium (SNCM) before the addition of CB essential oil. Cell morphology was assessed over 96 hours, and immunocytochemistry analyses were conducted for GFAP, GAP-43 and NeuN. Photomicrographs were made by scanning electron microscopy (SEM). Morphological analysis showed evident trophic development in the groups that received CB essential oil (P>0.000), immunoreactivity for GFAP, GAP-43 and NeuN and the plasticity of these cells were confirmed by SEM. This pioneer study about the plasticity of spinal cord neurons and glial cells opens new possibilities and techniques with essential oils for cell therapy in the presence of SNCM, which promoted neuroprotective action.